Does community cultural connectedness reduce the influence of area disadvantage on Aboriginal & Torres Strait Islander young peoples' suicide?. (11th November 2021) - Gibson, Mandy; Stuart, Jaimee; Leske, Stuart; Ward, Raelene; Vidyattama, Yogi
Abstract: Objective : The study aimed to examine associations of community cultural connectedness with Aboriginal and Torres Strait Islander young peoples' suicide rates in areas with elevated risk factors. Methods : Age‐specific suicide rates (ASSRs) were calculated using suicides recorded by the Queensland Suicide Register (QSR) of Aboriginal and Torres Strait Islander young people (aged 15–24 years) in Queensland from 2001–2015. Rate Ratios (RRs) compared young peoples' suicide rates in areas with high and low levels of cultural connectedness indicators (cultural social capital and Indigenous language use) within areas with elevated risk factors (high rates of discrimination, low socioeconomic resources, and remoteness). Results : Within low socioeconomically resourced areas and where Aboriginal and Torres Strait Islander people experienced more discrimination, greater engagement and involvement with cultural events, ceremonies and organisations was associated with 36% and 47% lower young peoples' suicide rates respectively (RR=1.57, 95%CI=1.13–2.21, p=<0.01; RR=1.88, 95%CI=1.25–2.89, p=<0.01). Within remote and regional areas, higher levels of community language use was associated with 26% lower suicide rates (RR=1.35, 95%CI=1–1.93, p=0.04), and in communities experiencing more discrimination, language use was associated with 34% lower rates (RR=1.53, 95%CI=1.01–2.37, p=0.04). Conclusion : Cultural connectedness indicators were associated with lower Aboriginal and Torres Strait Islander young peoples' suicide rates in communities experiencing the most disadvantage. Implications for public health : This provides initial evidence for trialling and evaluating interventions using cultural practices and engagement to mitigate against the impacts of community risk factors on Aboriginal and Torres Islander suicide.